DESEMPEÑO LABORAL EN EL DEPARTAMENTO DE TALENTO HUMANO EN EL GOBIERNO AUTÓNOMO DESCENTRALIZADO MUNICIPAL DEL CANTÓN BABAHOYO. - Ledesma Perez, Dayanara Alexandra (2019)
Municipal Autonomous Decentralized Government of the Babahoyo Canton is a public legal entity represented by the Mayor and managed jointly with the members of the Cantonal Council to attend, plan and execute public works, as well as to provide attention to the vulnerable groups of the Canton . This institution has political, administrative and financial independence and its purpose is based on the common good of the community and a case study has been carried out related to the work performance of the Human Talent department. The purpose of this case study is to determine the causes by which the work performance of the workers of the Human Talent Department of the Municipal Autonomous Decentralized Government of the Babahoyo Canton, is deficient.